Crucial Role of Water in the Mechanosynthesis of CsPbI3 and Other ABX3 Halides. Issue 55 (16th September 2020) - Tsvetkov, Dmitry; Mazurin, Maksim; Ivanov, Ivan; Malyshkin, Dmitry; Sereda, Vladimir; Zuev, Andrey
Abstract: Mechanochemical synthesis of CsPbI3, as a model system for ABX3 halides, was studied. Water was shown to strongly promote the kinetics of formation of CsPbI3 from the CsI+PbI2 mixture through increased mobility of the constituting ionic species. Since many binary and ternary halides are hygroscopic, it was concluded that the presence of small, uncontrollable and unintentional additions of water should often occur in both precursor mixtures and synthesized complex halides boosting the kinetics of formation of many, if not all, ternary organic–inorganic hybrid halides such as, for example, MAPbX3 (X=Cl, Br, I). In addition, trace amounts of water should influence the transport characteristics of complex halides. Thus, the presence of water explains, at least partially, the huge scatter in both the reported mechanochemical reaction times necessary for obtaining single‐phase APbX3 perovskite halides and the activation energies of ionic diffusion in APbX3 . Abstract : The crucial role of water, as a medium for fast diffusion of ions, in the mechanosynthesis of APbX3 (where A‐MA, Rb, Cs; X‐Cl, Br, I) halides was demonstrated. The presence of even a very small amount of water was shown to strongly promote a fast and reproducible synthesis of CsPbX3 halides. The optimum water content enabling obtaining phase‐pure CsPbI3 mechanochemically in a matter of 20–30 min was determined.